Regulating Pharmaceutical Prices in India Policy Design, Implementation and Compliance - Bhaskarabhatla, Ajay (India Studies in Business and Economics,, 2018)
This book presents an extensive study on the effectiveness of recent regulations on pharmaceutical prices in India, exploring the weaknesses in the design and implementation of pharmaceutical price controls and investigating what can be done to fix the broken system. In addition, it examines the extent to which essential medicines are actually made affordable by price controls. The book argues that companies make the pharmaceutical price control regime largely ineffective by coordinating to increase pre-regulation prices; by diversifying horizontally away from the regulated markets and increasing prices in the unregulated markets; by manipulating trade margins; and by refusing to comply with the regulation because the penalties remains negligible. The book draws on extensive empirical research involving India's 2013 Drug Price Control Order and widely-used medicines such as paracetamol and metformin to illustrate how firms have weakened regulation. It argues that the regulatory regime can be strengthened by using systematic analysis of product- and region-level data in the Indian pharmaceutical industry, and by screening for the strategies that firms currently employ to circumvent regulation. In closing, it discusses recent efforts to strengthen the implementation of price controls in India and expanding the scope of price controls to medical devices.